EFEKTIVITAS PENAMBAHAN EKSTRAK DAUN PEPAYA (Carica papaya L) UNTUK PENCEGAHAN Saprolegniasis PADA TELUR IKAN MAS PUNTEN (Cyprinus carpio) - Anis Zubaidah; Sri Samsundari; Muhammad Abdul Qodir Jaelani (Universitas Sriwijaya, 2021)
Pappaya leaf (Carica papaya L) contains antifungal and antibacterial compounds which can be applied to prevent transmission of Saprolegnia sp infections that attack carp eggs (Cyprinus carpio). The method in this study used several treatments, namely treatment A (control), B (papaya leaf extract 0.75 mg / l), C (papaya leaf extract 1 mg / l), D (papaya leaf extract 1.25 mg / l) and treatment of E (papaya leaf extract 1.5 mg / l). The results showed that there were significantly different treatments for the addition of papaya leaf extract to the hatching rate of carp punten eggs, with treatment C (1 mg / l) being the best treatment in increasing the hatching rate of 89.5%. Furthermore, the addition of papaya leaf extract to the prevalence of Saprolegnia sp fungi showed that treatment C (1 mg / l) was the best treatment in suppressing the prevalence of saprolegnia sp fungi with a prevalence rate of only 10.5%. Then the addition of papaya leaf extract to the goldfish survival rate showed a significant difference between treatments, with treatment C (1 mg / l) being the best treatment in increasing the value of Punten Carp survival arte with a survival rate of 94.68%. Therefore from this study it can be seen that the safe dose in the use of papaya leaf extract is to use a dose of 1 mg / l to suppress the prevalence of saprolegnia sp fungi and increase the hatching rate and increase the survival rate of the Punten Goldfish. Keyword: Saprolegnia sp, Papaya Leaves, Punten Carp